Factors Associated with Dyslipidemia among Workers: A Path Analysis - Fenita Indriani; Sumardiyono; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2025)
Background: The results of the 2023 Indonesian Health Survey show that 39.5% of the Indonesian population aged ≥ 15 years old have abnormal total cholesterol levels. Dyslipidemia or plasma lipid abnormalities play a major role in the pathogenesis of atherosclerosis on the walls of blood vessels which is the cause of coronary heart disease (CHD) and stroke. The purpose of the study was to analyze the factors that affect dyslipidemia in workers.Subjects and Method: This study uses an analytical observational design using a cross-sectional approach. The study was conducted at the Yogyakarta Labkesmas Center in October 2024 with a total of 150 worker study subjects. The sampling technique is non-probability sampling, namely total sampling. The independent variables in this study were BMI, glucose levels, stress, and depression while the dependent variables were total cholesterol levels. Data collection was carried out using secondary data and questionnaires, the data was analyzed by path analysis.Results: Each increase of one mg/dL of glucose level (b = 0.24; CI 95%= 0.09 to 0.39; p = 0.002) and one unit of depression (b = 0.16; CI 95%= 0.01 to 0.31; p= 0.043) will be followed by an increase in total cholesterol levels. Any increase in BMI through a mediator of glucose levels and stress through a mediator of depression will be followed by an increase in total cholesterol levels.Conclusion: Total cholesterol levels increase with increased glucose levels and depression levels. Total cholesterol levels are indirectly affected by BMI through glucose level mediators and stress levels through depression mediators.